Frontal Lobe Circuitry in Posttraumatic Stress Disorder - Lynn D. Selemon; Keith A. Young; Dianne A. Cruz; Douglas E. Williamson (Chronic Stress, 2019)
Symptoms of posttraumatic stress disorder include hyperarousal, avoidance of trauma-related stimuli, re-experiencing of trauma, and mood changes. This review focuses on the frontal cortical areas that form crucial links in circuitry pertinent to posttraumatic stress disorder symptomatology: (1) the conditioned fear extinction circuit, (2) the salience circuit, and (3) the mood circuit. These frontal areas include the ventromedial prefrontal cortex (conditioned fear extinction), the dorsal anterior cingulate and insular cortices (salience), and the lateral orbitofrontal and subgenual cingulate cortices (mood). Frontal lobe structural abnormalities in posttraumatic stress disorder, including volumetric reductions in the cingulate cortices, impact all three circuits. Functional analyses of frontal cortices in posttraumatic stress disorder show abnormal activation in all three according to task demand and emotional valence. Network analyses reveal altered amygdalo-frontal connectivity and failure to suppress the default mode network during cognitive engagement. Spine shape alterations also have been detected in the medial orbitofrontal cortex in posttraumatic stress disorder postmortem brains, suggesting reduced synaptic plasticity. Importantly, frontal lobe abnormalities in posttraumatic stress disorder extend beyond emotion-related circuits to include the lateral prefrontal cortices that mediate executive functions. In conclusion, widespread frontal lobe dysfunction in posttraumatic stress disorder provides a neurobiologic basis for the core symptomatology of the disorder, as well as for executive function impairment.